Relationship between muscle quality index and urinary incontinence among U.S. population: evidence from NHANES 2011 to 2014 - Hu, Yiwang; Xu, Hanyan; Xie, Shuying; Chen, Chengshui; Lei, Xiong (Frontiers in Endocrinology, 2025)
BackgroundUrinary incontinence (UI) is a common and troublesome global problem. The purpose was to explore the relationship between muscle quality index (MQI) and UI.MethodsWe performed a secondary analysis of the National Health and Nutrition Examination Survey (NHANES) database (2011 to 2014). Weighted logistic regression was used to analyze the relationship between MQI and UI. Subgroup analyses were further conducted to investigate the relationship. The P for trend and P for interaction were also conducted.ResultsA total of 2,779 participants were enrolled in the study, comprising 1,241 females and 1,538 males with a median age of 36 years. The prevalence of UI was approximately 25.45%. In adjusted model, weighted multivariate logistic regression analyses showed that MQI was significantly negatively associated with UI (OR,0.65; 95%CI,0.50 to 0.85). Furthermore, the results revealed that the highest MQI group had a 33% reduction in UI compared to the lowest MQI group and the P for trend was less than 0.05. In subgroup analysis, the MQI was negatively associated with UI in females (OR, 0.64; 95%CI, 0.45 to 0.92), under 40 years old (OR,0.65; 95%CI,0.50 to 0.85), poverty-to-income ratio of 1 to 3 (OR, 0.48; 95%CI, 0.29 to 0.78), and Non-Hispanic Black (OR, 0.50; 95%CI, 0.29 to 0.87), and in some populations without hypertension or diabetes.ConclusionThe study revealed that a higher MQI was associated with a lower prevalence of urinary incontinence. This study provides insights into potential preventive strategies for UI.